Effect of antipsychotic consumption during pregnancy on risk of gestational diabetes development: a systematic review and meta-analysis - Liu, Jingna; Zhao, Yanyan (Frontiers in Psychiatry, 2026)
BackgroundThe use of antipsychotic medications, including first-generation antipsychotics (FGAs) and second-generation antipsychotics (SGAs), during pregnancy has risen substantially. However, concerns remain regarding their potential metabolic effects, especially the risk of gestational diabetes mellitus (GDM).MethodsWe conducted a systematic review and meta-analysis of observational studies published up to 2025 that examined the association between maternal exposure to antipsychotics or antidepressants and the risk of GDM. Data were extracted independently by two reviewers, quality was assessed using the Newcastle–Ottawa Scale, and pooled relative risks (RRs) were calculated using a random-effects model.ResultsWe selected seventeen eligible studies, including large registry-based cohorts and prospective investigations across multiple countries. Pooled analysis demonstrated that maternal exposure to SGAs was significantly associated with an increased risk of GDM (RR = 1.59; 95% CI: 1.24–1.94), whereas FGAs showed no significant association (RR = 1.31; 95% CI: 0.29–2.32). The risk appeared greatest among women with continuous or multi-trimester exposure, particularly when exposure extended from first trimester into the third trimester. Funnel plot and Egger test showed no publication bias.ConclusionsThe higher risk of GDM seen with antipsychotic use was mainly linked to SGAs, while FGAs did not show the same effect. These findings emphasize the need to tailor treatment plans, closely monitor blood sugar levels, and involve a team of healthcare professionals when caring for pregnant women who require psychotropic medications.